Management of psychiatric complications in unrelated donor before unrelated peripheral hematopoietic stem cell collections - Hequet, Olivier (J Blood Med, 2016)
Allogeneic hematopoietic stem cell transplantation can efficiently treat patients with severe hematological diseases. A human leukocyte antigen-compatible donor is required for performing transplantation. The occurrence of unexpected acute severe diseases in a donor can compromise the feasibility of allogeneic hematopoietic stem cell transplantation. However, when a severe health problem occurs in a donor while the recipient has already received a conditioning regimen, hematologists have to find the best solutions for the recipient, while the team in charge of the donor has to find the best medical solutions for the donor. We describe here the occurrence of psychiatric acute complications in an unrelated donor while the myeloablative conditioning regimen had already been given to the recipient. We report the successive decisions that were made in an emergency based upon the expertise of physicians specialized in hematology, apheresis, cell therapy, and psychiatry to preserve the donor’s health and recipient’s life.